2018
DOI: 10.1590/0004-282x20180069
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation to Brazilian Portuguese of the Dementia Knowledge Assessment Tool Version Two: DKAT2

Abstract: The Brazilian Portuguese version was developed and the final version is suitable for use in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
4
10
0
Order By: Relevance
“…In this study, Alzheimer's disease (AD) was the most prevalent type (74.5%) of dementia, consistent with previously stated information about the most common cause of dementia. 23 This study showed that the majority of caregivers were female (79.1%) and, in accordance with other studies, 68.1% of these were daughters of the patients. 23,24 In a comprehensive review of studies examining adherence to dementia medication, it was indicated that adherence ranged from 34% to 94%, consistent with the rate of adherence found in the first interview of this study (70.2%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, Alzheimer's disease (AD) was the most prevalent type (74.5%) of dementia, consistent with previously stated information about the most common cause of dementia. 23 This study showed that the majority of caregivers were female (79.1%) and, in accordance with other studies, 68.1% of these were daughters of the patients. 23,24 In a comprehensive review of studies examining adherence to dementia medication, it was indicated that adherence ranged from 34% to 94%, consistent with the rate of adherence found in the first interview of this study (70.2%).…”
Section: Discussionsupporting
confidence: 91%
“…23 This study showed that the majority of caregivers were female (79.1%) and, in accordance with other studies, 68.1% of these were daughters of the patients. 23,24 In a comprehensive review of studies examining adherence to dementia medication, it was indicated that adherence ranged from 34% to 94%, consistent with the rate of adherence found in the first interview of this study (70.2%). One of the most important findings of this study is a 25.5% improvement in the rate of patients with high adherence to dementia medications after clinical pharmacist intervention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, most caregivers were female and had a mean age of 56.0 years, consistent with data observed in other studies. 5,10,11 Caregivers' average education level was 8.0 years of schooling, results evidenced in national studies. 12,13 However, in an international study carried out in Faro (Portugal) involving 110 informal caregivers for dependent elderly found that most caregivers (67.3%) had four years or less of education, characterizing a low education profile.…”
Section: Discussionmentioning
confidence: 85%